Pola Pendidikan Berkemajuan - Rusman, Rusman (Fakultas Agama Islam, 2016)
Outdoor life and human life and human is willing to accept the influence of the outside world, ready to communicate with the possibility of exchange of alternatives patterns of thought and behavior deeds. Criteria level of openness of human and moral life of society is determined by the level by level or speed tempo changes and problems faced. Patterns of thought and behavior that is based on the open view of cultural relativity and pluralism or diversity of truth and reality. Instead of society and human beings against which to be covered is marked by a denial of justice could have taken third and only one true law used as guidelines in determining the truth about reality, either about to culture-an, patterns of thought and behavior deeds. In many ways and basically the truth and reality possessed rated dignified absolute, applies whenever and wherever. Resulting symptoms conservative attitudes which do not want changes that may be as a result of the influence that comes from the outside world and different.There are three educational social problems that lead to educational berkemajuan namely: (1) Problems of social progress of students, (2) Problems teacher social progress, and (3) Problems of social advancement of educational institutions (schools). Of these problems can be overcome by implementing three patterns: (1) Pattern nomothetic, (2) Patterns idiographic, and (3) Transactional Pattern.Their harmonious and balanced cooperation, give and receive mutual control and control between teacher education institutions and schools in order devotion to children, students and the development of education in general, will determine much of the future development of the communities.